Improved Preservation of Saphenous Venous Conduits by the Use of Papaverine mixed heparinized blood Solution during Harvesting - Maruf, MMF; Sabur, SAMA; Akter, T; Hakim, E; Ahsan, NAK (Cardiovascular Journal, 2012)
Background: High-pressure distension during harvesting damages the saphenous vein (SV) and may contribute to subsequent coronary artery bypass graft (CABG) occlusion. Application of vasodilator agents to the SV during harvesting may reduce the need for high-pressure distension and improve graft quality. We tested the effects of a vasodilator solution containing the conventional agent papaverine (Pap) mixed with heparinized blood on the pressure necessary to overcome SV spasm and on the structure. Methods: 150 patients undergoing CABG were nonrandomly allocated to receive an application of either intraluminal papaverine (Pap) mixed with heparinized blood(Group-A), or intraluminal heparin mixed normal saline(group-B) to the SV for distension during harvesting. The peak pressures required to distend the vein were recorded. Samples of SV were taken for microscopical analysis just before we performed the anastomosis. Results: The results for mean peak pressures (mm Hg) were: Normal saline 131.77±20.6 (range 85 to199 mmHg); and Papaverine mixed blood solution, 56.4±2.1 (range 40 to 90 mmHg); P<0.001, (Pap mixed blood solution versus normal saline); The results of histological study for endothelial injury were: Normal saline, 52.5 %; Papaverine mixed blood solution , 20%; (P<.02, untreated versus Pap mixed blood solution). Conclusions: Intraluminal use of Papaverine mixed heparinized blood solution during vein harvesting requires low distension pressure and improves endothelial coverage compared with the use of heparin mixed normal saline. Key Words: Venous Grafts; CABG; Papaverine DOI: http://dx.doi.org/10.3329/cardio.v4i1.9382 Cardiovasc. J. 2011; 4(1): 3-7